2023
DOI: 10.1037/sgd0000485
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of the experiences of sexual and gender minority students in school psychology programs.

Abstract: This study explored the potential barriers to the success of sexual and gender minority (SGM) students in school psychology programs by assessing their experiences in academic and professional environments. The sample consisted of 34 SGM and 170 non-SGM school psychology graduate students in the United States. Results revealed that SGM and non-SGM students reported similar levels of academic engagement, peer and faculty support, self-efficacy, and perceived stress. However, SGM students, when compared to non-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…STEM undergraduate programs and environments are typically founded upon hetero- and cis-normative standards and can be unwelcoming of other gender identities and sexualities [ 5 8 ]. Specifically, SGM students often deal with discrimination and exclusion due to others’ perceptions, biases, and stereotyping of their minoritized sexual and gender identities [ 5 , 9 , 10 ]. This treatment is frequently in the form of microaggressions—covert, indirect, restrained, and ambiguous demonstrations of discrimination and prejudice against minoritized groups [ 6 , 11 , 12 ], such as cis-normative language use by faculty [ 13 ], including their resistance to trans or non-binary students’ pronouns [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…STEM undergraduate programs and environments are typically founded upon hetero- and cis-normative standards and can be unwelcoming of other gender identities and sexualities [ 5 8 ]. Specifically, SGM students often deal with discrimination and exclusion due to others’ perceptions, biases, and stereotyping of their minoritized sexual and gender identities [ 5 , 9 , 10 ]. This treatment is frequently in the form of microaggressions—covert, indirect, restrained, and ambiguous demonstrations of discrimination and prejudice against minoritized groups [ 6 , 11 , 12 ], such as cis-normative language use by faculty [ 13 ], including their resistance to trans or non-binary students’ pronouns [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…We reasoned that individuals with minoritized identities would encounter common issues navigating dating apps as other HSP graduate students. We also reasoned that students with minoritized identities would face unique challenges pertaining to their identities and intersections of those identities with other aspects of identity or location (e.g., living in a small college town as a sexual minority), consistent with work suggesting that sexual and gender minority HSP students feel less supported by their programs than heterosexual/cisgender students (Chen et al, 2021).…”
mentioning
confidence: 76%
“…This is consistent with previous research (e.g., Nilsson & Schmidt, 2005) that found that individuals from marginalized groups show greater interest in social justice advocacy. The limited research on sexual orientation in school psychology suggests that graduate students may not perceive sexual marginalized individuals to be an oppressed group (McCabe & Rubinson, 2008) and that sexual marginalized graduate students perceive that academic and professional environments are less welcoming to them (Chen et al, 2023). For these reasons, sexual marginalized students may be more aware of the need for social justice and thus hold more positive attitudes about social justice.…”
Section: Discussionmentioning
confidence: 99%
“…While this finding was unexpected, previous research suggests that those with privileged social identities may understand how to leverage their privilege to advance social justice goals and feel more efficacious (Beer et al, 2012). Another possibility is that sexual marginalized students may feel like they have less power to engage in social justice advocacy due to concerns about professional repercussions (e.g., loss of employment) and an unsupportive professional environment (Chen et al, 2023; McCabe & Rubinson, 2008). The significant contribution of the multicultural competence variables suggests that cultural awareness, knowledge, and skills may help graduate students become more confident in their ability to act in ways that support social justice and enhance preexisting commitments to social justice.…”
Section: Discussionmentioning
confidence: 99%